On the systematic placement of Montezumellidae Ossó & Domínguez, 2013 (Decapoda: Brachyura: Eubrachyura) - Ossó, Àlex; Domínguez, José Luis (Zootaxa, 2019)
Recovery of new samples of Montezumella amenosi Vía, 1959 and Moianella cervantesi Ossó & Domínguez, 2013, with preserved cephalic appendages and ventral features, now allows for new and complete revision of Montezumellidae, an extinct eubrachyuran family that appeared in the Middle Eocene and lived until the Neogene. New data on antennular and antennal features, as well as additional data on the sternal and pleonal features of the females, have been analyzed. As a result, Montezumellidae is removed from Cancroidea, where it was previously placed. In view of the unique set of characters that this family presents, no other superfamily of Eubrachyura, fossil or recent, can accommodate it. Therefore, a new superfamily is proposed for it. Despite several basal characters that this group presents, its possible origins or phylogenetic relationships are not clear. Neither, based on the present fossil record, no relationships with potential ancestors or descendants can be suggested.